FACTORS AFFECTING THE CRISIS IN CENTRAL ASIA (From Ancient Times To The Middle Ages) - Sharifov Ehronbek Erkin o`g`li (International Journal on Human-Computing Studies, 2022)
This article describes the dynasties and states that ruled Central Asia and the factors that led to the disintegration or collapse of state governance. The period covered in the article focuses on the dynastic states with a centralized state system in the Central Asian region from antiquity to the middle ages.